A parametric study on exergetic sustainability aspects of high-pressure hydrogen gas compression. (22nd March 2016) - Ozsaban, Mert; Midilli, Adnan
Abstract: This paper presents a parametric study on exergetic sustainability aspects of high-pressure-hydrogen gas compression process in terms of exergy. In this regard, a single stage, two-stage, three-stage and four-stage-hydrogen gas compression processes have been considered to make a parametric evaluation in terms of the exergetic sustainability parameters including i) exergetic efficiency, ii) waste exergy ratio, iii) exergy recoverability ratio, iv) exergy destruction ratio, v) environmental effect factor, vi) exergetic sustainability index. Here, hydrogen is assumed to be a real gas because of higher pressures, and therefore, its compressibility factor is taken into account thorough the calculations. Accordingly, it is noticed that increasing stage number (ranging 1 to 4) and hydrogen gas inlet pressure (from 1 to 200 bar) decrease waste exergy ratio (from 0.853 to 0.058) and environmental effect factor (from 5.789 to 0.061) while going up exergetic sustainability index (from 0.173 to 16.337). However, increasing compressor-outlet pressure of hydrogen gas (ranging from 200 to 900 bar) reduces exergetic sustainability index (from 7.472 to 1.069) while going up waste exergy ratio (from 0.118 to 0.483), exergy destruction ratio (from 0.089 to 0.253), environmental effect factor (from 0.134 to 0.936), and exergy recoverability ratio (from 0.029 to 0.230).